Perancangan Interior Rumah Makan Khas Medan dan Kongkow Khas Medan di Surabaya - Amanda Amanda; Sriti Mayang Sari (Intra, 2014)
Restaurant and kongkow place are a unity when talked about residents from Medan city. These became a problem for those migrants from Medan city in Surabaya city because of the lack of places for kongkow avtivity. So there’s needs for a restaurant that also can accomodate kongkow activity. This restaurant applied interior atmosphere that adapted from street atmosphere based from Medan city residents’s habit to kongkow outside. This restaurant is espected to become a place for all Medan city migrants in Surabaya city gather up or even introduce Medan city’s food to Surabaya city resident.